STRATEGY THE EFFECT OF INNOVATION, IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT (TQM) AND ENTREPRENEURSHIP ORIENTATION ON COMPETITIVE ADVANTAGE STRATEGIES IN BUILDING COMPANY PERFORMANCE (Study on Small and Medium Enterprises (SMEs) in the Fish Processing Industry in Semarang City) - Muhammad Zuhal Hilmiand; Mahfudz Mahfudz (Jurnal Akuntansi dan Pajak, 2023)
Companies that have competitive advantages will certainly be pioneers in business competition, which can have a positive impact on company performance. This study analyzes the factors that affect the performance of fish processing SME companies in the city of Semarang namely Innovation (X1), Total Quality Management (X2), Entrepreneurship Orientation (X3), and Competitive Advantage as intervening. Based on the research problem, namely how to increase Competitive Advantage so that it has a positive impact on Company Performance and the factors that influence Competitive Advantage, namely Innovation, Total Quality Management, and Entrepreneurship Orientation. The sample of this study amounted to 50 respondents who were then given a questionnaire to be answered by the respondent and overall the questionnaire could be returned, resulting in a final questionnaire of 50 respondents. Determination of the sample is carried out by the census method, which provides equal opportunities to the research population. In this study, the respondents were the Owners of Processed Fish SMEs in Semarang City. The tools used to analyze the data arePartial Least Square (PLS) 3.0 with the method of Structural Equation Modeling (SEM). The results of this study indicate that there are 2 rejected hypotheses and 5 accepted hypotheses from 7 hypotheses in the study. The factors that have a significantly positive effect are Innovation (X1), Total Quality Management (X2), Entrepreneurship Orientation (X3) to Competitive Advantage (Y1) and factors that directly influence significantly the Company's Performance (Y2) are Entrepreneurial Orientation. Innovation and Total Quality Management have no significant effect on Company Performance. Keywords: Innovation, Total Quality Management, Entrepreneurship Orientation, Competitive Advantage, and Company Performance